O Brasil visto como um estado de bem-estar social de renda média e com uma commodity-currency: Fatos e um modelo macroeconômico de curto prazo - Claudio Hamilton Matos dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The text calls attention to two structural features of the Brazilian economy, i.e., the facts that the country has built a very impressive welfare state (WS) over the years, one that looks as strong and mature as ever, and that the Brazilian Real (R) apparently has become a "commodity-currency" over this century, meaning that it tends to appreciate when (a selected basket of) world commodity prices in US dollars go(es) up. It is argued that, although relatively neglected in the literature, both features play key roles in the functioning of the Brazilian economy both in the short and the medium runs. A formal short period model of the economy - that is compatible with and fits actual Brazilian national accounts data - is presented to make the argument clear. Insights based on the model are then used to produce plausible medium run dynamic trajectories in which commodity prices and WS institutions interact in meaningful ways.
Keywords: E12; O54; F41; 330; welfare state; commodity-currency; Brazilian economy; commodity prices; exchange rate depreciation